Optimal taxation of human capital - Braun, Christoph (Technische Universität Dortmund, 2011)
This dissertation is on optimal taxation of human capital and tackles the following leading question: How should the tax system be optimally designed to promote the accumulation of human capital to maximize economic well- being? Chapter 2 discusses results derived by Bovenberg and Jacobs (2005) and Richter (2009), who show the education efficiency theorem: In a second-best optimum, the education decision is undistorted if the function expressing the stock of human capital features a constant elasticity with respect to education. I drop this assumption. The household inherits an initial stock of human capital, implying that the aforementioned elasticity is increasing. In a two-period Ramsey model of optimal taxation, I show that the education efficiency theorem does not hold. In a second-best optimum, the discounted marginal social return to education is smaller than the marginal social cost. The household overinvests in human capital relative to thefirst best. The government effectively subsidizes the return to education. Chapter 3 studies a Ramsey optimal taxation model with human capital in an infinite-horizon setting. Contrary to Jones, Manuelli, and Rossi (1997), the human capital production function does not include the current stock of human capital as a production factor. As a result, the return to human capital, namely labor income, does not vanish in equilibrium. In a stationary state, the household underinvests in human capital relative to the first best, i.e., education is distorted. Human capital is effectively taxed. The optimal tax scheme prescribes making the cost of education not fully tax-deductible. Chapter 4 studies second best policies for education, saving, and labour in an OLG model in which endogenous growth results from human capi- tal accumulation. Government expenditures have to be financed by linear instruments so that growth equilibria are inefficient. The inefficiency is exacerbated if selfish individuals externalize the positive effect of education on descendents' productivity. It is shown to be second best to subsidize edu- cation even relative to the first best if the elasticity of the human capital investment function is strictly increasing. The analysis allows one to iden- tify fundamental differences in the efficient dynamic taxation of human and nonhuman capital. Chapter 5 presents a numerical analysis of chapter 4's underlying model with selfish individuals. It turns out that the case for subsidizing education to account for distortionary labor taxation is rather weak. The still dominant justification for subsidizing education is to internalize intergenerational externalities.
Keywords: Human capital; Optimal taxation; Ramsey approach; 330; Humankapital / Ausbildung / Optimale Besteuerung